Expression of (NM23-H1) gene in acute lymphocytic leukemia and its clinical significance - Ansary, Mervat M. El; Allah, Nagwa Abd; Emara, Nahed A.; Tablawy, Manar M. el; Mahmoud, Shereen (Archives of Medical Science, 2009)
Introduction: The aim of this article is to determine the expression of the NM23-H1 gene in acute lymphocytic leukaemia, and to evaluate the relationship between NM23-H1 expression, clinical features and laboratory features. Material and methods: The study included 25 newly diagnosed ALL patients and a control group of 10 age- and sex-matched healthy individuals with no family history of leukaemia. All patients and controls were subjected to careful history taking, complete blood picture, bone marrow aspirate examination, cytochemistry (peroxidase and Sudan black) and immunophenotyping (using the ALL panel to detect B cell markers and T cell markers). Venous blood samples from patients and controls were analysed for NM23-H1 mRNA expression level by real time PCR. Results: NM23-H1 mRNA was overexpressed in ALL cases compared to the control group, with a mean level of 0.99 ±0.74, 0.22 ±0.16 respectively. The resistant cases expressed a significantly higher NM23-H1 level (mean 0.975) than those who achieved remission (mean 0.805), and passed out cases expressed a highly significant level of the studied gene (mean 1.780). Conclusions: There is a highly significant positive correlation between the level of expression of the NM23-H1 gene and the outcome of patients with ALL.